Imbalance between plasma double-stranded DNA and deoxyribonuclease activity predicts mortality after out-of-hospital cardiac arrest. (June 2020) - Ondracek, A.S.; Hofbauer, T.M.; Wurm, R.; Arfsten, H.; Seidl, V.; Früh, A.; Seidel, S.; Hubner, P.; Mangold, A.; Goliasch, G.; Heinz, G.; Lang, I.M.; et al.
Abstract: Aim: Despite an increased rate of return of spontaneous circulation (ROSC) in out-of-hospital cardiac arrest (OHCA) patients, almost half of patients do not survive up to hospital discharge. Understanding pathophysiological mechanisms of post-cardiac arrest syndrome is essential for developing novel therapeutic strategies. During systemic inflammatory responses and concomitant cell death, double-stranded (ds) DNA is released into circulation, exerting pro-inflammatory effects. Deoxyribonuclease (DNase) degrades dsDNA. The role of DNase activity in OHCA survivors and impact on clinical outcome has not been analyzed yet. Methods: In a prospective, single-center study, dsDNA and DNase activity were determined at hospital admission (acute phase) and 24 h (subacute phase) after ROSC. The ratio between dsDNA levels and DNase activity was calculated to determine the extent of dsDNA release in relation to the patients' capacity of degradation. Thirty-day mortality was defined as study end point. Results: We enrolled 64 OHCA survivors, of whom 26.6% ( n  = 17) died within 30 days. A peak of circulating dsDNA was observed at admission which decreased within 24 h. DNase activity did not differ between acute and subacute phase, while dsDNA load per DNase activity significantly decreased. The ratio between dsDNA levels and DNase activity in the subacute phase was the strongest predictor of 30-day mortality with an adjusted HR per 1 SD of 3.59 (95% CI, 1.80–7.18, p  < 0.001). Conclusion: Disproportionally increased dsDNA levels uncompensated by DNase activity are a strong predictor of mortality in OHCA survivors. This pilot study points to a potentially protective effect of DNase activity in patients undergoing cardiac arrest.